Profil Kesulitan Belajar Peserta Didik Kelas XI F SMA Negeri 2 Kinali Kabupaten Pasaman Barat - Fauzanni, Santika; Candra, Yasrial; Rahma Mulyani, Rila (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
This research is motivated by the low success of students in learning. The purpose of this study is to describe the learning difficulties experienced by class XI students at SMA Negeri 2 Kinali, West Pasaman Regency. This research is a descriptive study using a quantitative approach. The research sample was all students in Class XI F3 totaling 31 people. The data collection technique used was a questionnaire consisting of 33 statements. The results of the study showed learning difficulties in the categories: 1) Learning disorders with an average score of 22.61 or a fairly high category, 2) Learning disorders with an average of 22.87 in the fairly high category 3) Learning dysfunction with an average of 16.09 in the fairly high category 4) Low achievement (under achiever) with an average of 21.77 in the fairly high category 5) Slow learner with an average of 24.42 in the low category. 6) Learning difficulties from all aspects experienced by students with an average score of 107.77 or in the fairly high category. Based on these data, it can be concluded that the learning difficulties of students in class XI at SMA Negeri 2 Kinali, West Pasaman Regency are in the fairly high category.